Cultivating Professionalism in Saudi Arabian Neurology Residency Programs: The Impact of Case-Based Learning - Alrawdhan N; Althubaiti A; Alzahem A; Alqahtani S; Baarmah D; Alrumayyan A (Advances in Medical Education and Practice)
Nada Alrawdhan,1 Alaa Althubaiti,2 Abdullah Alzahem,3 Salma Alqahtani,4 Duaa Baarmah,5 Ahmed Alrumayyan6 1Department of Audiology and Speech Pathology, College of Applied Medical Sciences, King Saud Bin Abdulaziz University for Health Sciences, King Abdullah International Medical Research Center, Riyadh, Saudi Arabia; 2College of Medicine, King Saud bin Abdulaziz University for Health Sciences, King Abdullah International Medical Research Center, Jeddah, Saudi Arabia; 3Department of Medical Education, College of Medicine, King Saud Bin Abdulaziz University for Health Sciences, King Abdullah International Medical Research Center, Riyadh, Saudi Arabia; 4Movement Disorders Program, Neuroscience Center, King Faisal Specialist Hospital and Research Center, Riyadh, Saudi Arabia; 5Pediatric Department, King Abdullah bin Abdulaziz University Hospital, College of Medicine, Princess Nourah Bint Abdulrahman University, Riyadh, Saudi Arabia; 6College of Medicine, King Saud Bin Abdulaziz University for Health Sciences, King Abdullah International Medical Research Center, Riyadh, Saudi ArabiaCorrespondence: Nada Alrawdhan, Department of Audiology and Speech Pathology, College of Applied Medical Sciences, King Saud bin Abdulaziz University for Health Sciences, P.O. Box 3660, Riyadh, 11481, Saudi Arabia, Tel +966 11 429 999 999 Ext. 98204, Email Rawdhann@ksau-hs.edu.saPurpose: There is no universally accepted definition of medical professionalism, making it challenging to identify the most effective teaching methods for embedding professionalism within postgraduate residency curricula. This study aimed to evaluate the effectiveness of case-based learning (CBL) in teaching professionalism to neurology residents at two training centers in Saudi Arabia. An additional objective was to assess the residents’ knowledge of professionalism.Methods: A pre- and post-test design was utilized using the Penn State College of Medicine Professionalism Questionnaire, which was administered to all neurology residents at the two participating hospitals. This approach measured the changes in residents’ understanding of professionalism before and after they participated in three consecutive weeks of CBL sessions. Theses sessions included interactive case discussion aimed at enhancing their understanding of professionalism.Results: Neurology residents exhibited significant improvements in several professionalism domains after interventions. The experimental group showed marked enhancements in accountability (P=0.002, effect size=0.59) and duty (P=0.018, effect size=0.46). The control group, after CBL sessions, improved significantly in altruism (P=0.0008, effect size=0.64) and honor/integrity (P=0.018, effect size=0.45). Post-intervention, the experimental group demonstrated superior altruism compared to the control group pre-intervention (P=0.03, effect size=0.40).Conclusion: The observed improvements in various aspects of professionalism indicate that case-based learning is an effective method for bolstering neurology residents’ understanding and knowledge of professionalism. This finding supports the inclusion of CBL in residency curricula to foster professional development.Keywords: medical professionalism, case-based learning, residency programs, neurology education, postgraduate